Comparative transcriptomics analysis reveals a calcineurin B‐like gene to positively regulate constitutive and acclimated freezing tolerance in potato. (12th September 2022) - Chen, Lin; Zhao, Hongbo; Chen, Ye; Jiang, Fujing; Zhou, Feiyan; Liu, Qing; Fan, Yongqi; Liu, Tiantian; Tu, Wei; Walther, Dirk; Song, Botao
Abstract: Freezing stress is a major limiting factor in crop production. To increase frost‐hardiness of crops via breeding, deciphering the genes conferring freezing‐tolerance is vital. Potato cultivars ( Solanum tuberosum ) are generally freezing‐sensitive, but some potato wild species are freezing‐tolerant, including Solanum commersonii, Solanum malmeanum and Solanum acaule . However, the underlying molecular mechanisms conferring the freezing‐tolerance to the wild species remain to be deciphered. In this study, five representative genotypes of the above‐mentioned species with distinct freezing‐tolerance were investigated. Comparative transcriptomics analysis showed that SaCBL1‐like ( calcineurin B‐like protein ) was upregulated substantially in all of the freezing‐tolerant genotypes. Transgenic overexpression and known‐down lines of SaCBL1‐like were examined. SaCBL1‐like was shown to confer freezing‐tolerance without significantly impacting main agricultural traits. A functional mechanism analysis showed that SaCBL1‐like increases the expression of the C‐repeat binding factor ‐regulon as well as causes a prolonged higher expression of CBF1 after exposure to cold conditions. Furthermore, SaCBL1 – like was found to only interact with SaCIPK3–1 (CBL‐interacting protein kinase) among all apparent cold‐responsive SaCIPKs. Our study identifies SaCBL1‐like to play a vital role in conferring freezing tolerance in potato, which may provide a basis for a targeted potato breeding for frost‐hardiness. Summary statement: To increase frost‐hardiness of potato via breeding, deciphering the genes conferring freezing‐tolerance is essential. Freezing‐tolerant and sensitive potato genotypes were characterized experimentally and SaCBL1 ‐ like was identified to positively regulate constitutive and cold‐acclimated freezing tolerance in potato.